Peningkatan Pengetahuan Kb Implant dan Pemasangan KB Implant di Pustu Duampanua Kecamatan Anreapi Kabupaten Polewali Mandar - Firna, Fransiska; Sumiyati, Sumiyati; Niar, Niar; Safitry, Rusni (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The main problem in Indonesia is the high population growth rate, this problem can be prevented by using effective contraceptives that have long-term effects, one example is the use of KB Implants. Family Planning is one of the most basic and primary preventive health services for women. Implants are Long-Term Contraceptive Methods (MKJP) made of plastic rubber containing hormones, installed on the upper arm. Implants can be used for a long period of 3-5 years and are reversible. The purpose of this community service activity is to increase knowledge in WUS and PUS regarding long-term contraceptives and to help run the MKJP Program. The implementation of this Community Service activity was attended by 30 WUS and PUS in the Anreapi Health Center Work Area. The methods used in this activity are through lectures, discussions, questions and answers, and installation of Implant contraceptives. This activity is to increase the understanding of WUS and PUS regarding long-term contraceptives.